Pattern of household access to water supply in sub-urban settlements in parts of Lagos State, Nigeria - Akoteyon, Isaiah Sewanu (Faculty of Social Sciences and Humanities, UKM,Bangi, 2016)
Access to safe water supply is one of the fundamental basic needs for human survival. This study examined patterns of household access to water supply in sub-urban settlements in parts of Lagos State,Nigeria.Data used for this study were obtained from social survey on access through questionnaire administration of randomly sampled 200 household members from four settlements each from Badagry and Ikorodu local government areas during the month of September 2012.The results showed that, boreholes, protected dug wells, vendors providing water, and rainwater harvesting were the main sources of water in the study area. Access to improved water source revealed that Igbogbo, a settlement from Ikorodu had the highest score with about 16.1%. About 21.7% of the households have access to safe water. A dependent relationship was established at p<.000 between the settlements and safe water sources. The pattern of access to improved water source showed that, households from Iworo-Ajido and Igbogbo had the highest access in Badagry and Ikorodu local government areas respectively. The attributes of water access showed about 60%, 79.8%, 42.7% and 62.1% of the respective households gained access to water based on distance, time taken, number of trips and quantity of water consumed per capita per day. The study concluded that access to safe water supply was low in the area. It recommended rainwater harvesting technology, extension of piped water connections and public standpipes for safe water supply provision to the suburb settlements.